Rancang Bangun Charger Berbasis PLTS - Wijaya, Rahmat Dhani; Wahyudi, Agus; Aditya, Fensa Vio; Ardafans, Farizal Yusuf Varel; Pratama, Yongky (CV. SINAR HOWUHOWU, 2025)
Solar energy is one of the most potential renewable energy sources in tropical areas such as Indonesia. Its utilization is carried out through a Solar Power Plant (PLTS) system consisting of solar panels, solar charge controllers (SCC), batteries, and converters. Solar panels convert light energy into electricity using the principle of the photovoltaic effect, with a conversion efficiency of around 15–20%. The energy generated is controlled by a PWM type SCC before being stored in a 12V 65Ah dry battery. To meet the needs of charging devices such as mobile phones, the system is equipped with a step-down converter and fastcharging module that can adjust the output to 3–12V. [1] The installation system also pays attention to electrical safety standards, including the selection of cables and the use of MCBs according to PUIL 2000. This system shows great potential in providing efficient and environmentally friendly alternative electrical energy.